Anodic dissolution of cobalt in aqueous sodium nitrate solution at high current densities. Issue 6 (23rd May 2014) - Schneider, M.; Schubert, N.; Höhn, S.; Michaelis, A.
<x xml:space="preserve">Abstract</x> The present work focuses on the anodic dissolution of cobalt and the surface texture development in 2.9 mol/L sodium nitrate solution under current controlled conditions at 25 and 30 A/cm2. Before the electrochemical experiments the crystallographic orientation of the samples was investigated by EBSD. The anodic behavior of cobalt as well as the surface topography was microscopically observed using a special electrochemical through flow cell in‐operando during the current controlled dissolution. The experiments were completed by SEM/EDX‐analysis. The authors evidence that the dissolution process at high current densities is independent of the crystallographic orientation of the sample and leads to a surface polishing. The current efficiency is approximately 100%. Only a weak and temporary oxygen evolution was detected at 25 A/cm2.